Pengaruh Kepemimpinan, Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Bank Kaltim Samarinda - Dyah Kusrihandayani (Jurnal Ilmiah Aset, 2017)
The influence of the leadership, work environment and motivation to employee performance Bankaltim Main Branch Samarinda. Employees are the main force to achieve its goals. So companies need employees who have the ability and expertise both to achieve the company’s goals. As a logical consequence of these demands, this research led him to learn how to improve employee performance through leadership, work environment, and work motivation. The purpose of this study to prove and explain the influence of leadership, work environment and work motivation on employee performance Bankalrim Main Branch Samarinda. The study population was all employees at the Main Branch Bankaltim Samarinda amounted to 242 people. Samples taken in this study is the number of employees 151 people, sample calculations performed using the formula Slovin with an error tolerance level of 5%. Collect data through questionnaires using Likert scala with statistical analysis using multiple linier regression analysis. The result showed that : 1. Leadership significant effect on employee performance, 2. Work environment a significant effect on the performance of employees, 3. Motivation significant influence on employee performance, 4. Leadership, work environment and work motivation significant effect on the performance of employees.